Factors influencing consumer intention to adopt social media for planning food tour in Klang Valley - Chong, Chun Hong (2023)
The main objective of this research is to determine the factors that influence consumers intention to adopt social media for planning food tour in Klang Valley. In this paper, researcher has investigated the relationship between perceived usefulness, perceived trust, perceived ease of use, media richness and consumer intention to adopt social media for planning food tour in Klang Valley. In addition, this research also tested which factor has the highest influence on this phenomenon.